Tracking trachyte on the Roman routes: Provenance study of Roman infrastructure and insights into ancient trades in northern Italy. Issue 4 (30th November 2017) - Germinario, Luigi; Zara, Arturo; Maritan, Lara; Bonetto, Jacopo; Hanchar, John M.; Sassi, Raffaele; Siegesmund, Siegfried; Mazzoli, Claudio
Abstract: Roman colonization of northern Italy during the late Republican Age brought about significant building activity in the newly acquired territories, involving the construction of new infrastructure that demanded large amounts of stone. Trachyte of the Euganean Hills was among the most commonly used materials for building roads, bridges, forum squares, and aqueducts. This paper addresses the recognition of the provenance quarry of Euganean trachyte used in Roman public infrastructure in northeastern Italy. Petrographic features and major‐ and trace‐element composition of bulk rock and phenocrysts, analyzed by X‐ray fluorescence (XRF) and laser ablation inductively coupled plasma mass spectrometry (LA‐ICPMS), were used as provenance tracers. The provenance determinations allow for exploring the commercial, political, and economic dynamics involving the supply of trachyte for public works, and the management of Roman quarries, which likely were in competition with each other and separately controlled by the most important nearby cities. Finally, broad insights into ancient trades in northern Italy and the main routes of stone distribution are discussed: most transport was done by ship, being more rapid and less costly, taking advantage of the Adriatic Sea, the Po River, and the many waterways close to the Euganean quarries.